GW24-e2246 Predictors of long-term outcome in angiographically confirmed stent thrombosis. (1st October 2013) - Mi, Jie; Zhang, Chun-Xiao; Sun, Zhong-Hua; Zhong, Ming-Hui; Tian, Gang; Huang, Ping; Zang, Xi-Wen; Chen, Tao; Fan, Rui-Juan; Qi, Xiang-Qian
Abstract : Objectives: To identify the predictors of long-term outcome in consecutive patients with angiographically proven stent thrombosis (ST). Methods: Consecutive patients with angiographically proven ST in our centre were enrolled from January 2005 to December 2011. Demographic data, medical history, electrocardiography findings, ultrasound findings, laboratory test results and treatments administered to patients were collected. The primary endpoint of the study was cardiac death. Major adverse cardiac events (MACE) included cardiac death, recurrent definite ST, non-fatal myocardial infarction (MI) and target-vessel revascularisation (TVR). Cox regression analysis was applied to assess the association between variables and cardiac death and MACE. Results: Four-nine patients with angiographically proven ST were reported in our centre from January 2005 to December 2011. Among them, 5 patients (10.2%) died from cardiac-related causes in hospital. Until September 30, 2012, 44 patients accepted follow-up. The average follow-up time was 1149.3 ± 710.1 days (274 to 2824 days). The in-hospital and one-year mortality were 10.2%, and 12.4% respectively. The cumulative incidence of in-hospital development of MACE was 12.2%. And the incidences at 2, 4 and 5 years were 18.5%, 24.8%, and 37.3%, respectively. Our study showed that family history of coronary artery disease (CAD) and two-vessel ST could be used as independent predictors of cardiac death (hazard ratio 27.70, 95% CI 2.34 to 328.81, P = 0.008 and 20.04, 95% CI 1.63 to 246.16, P = 0.019, respectively), and they could be used to predict MACE (hazard ratio 8.76, 95% CI 2.50 to 30.70, P = 0.001 and 9.21, 95% CI 1.73 to 49.19, P = 0.009, respectively) as well. Conclusions: Patients who suffered from ST were considered to have a poor prognosis. In addition, family history of CAD and simultaneous two-vessel ST were associated with the cardiac death and MACE.